Job and personal resources: boosting work engagement and job satisfaction in hospitals - Kalsum, Ummu; Rivai, Fridawaty; Maidin, Alimin; AS, Andi Indahwaty; Zulkifli, Andi; Thamrin, Yahya (Intelektual Pustaka Media Utama, 2024)
The low level of job satisfaction (JS) among hospital staff is associated with the low level of work engagement (WE). To examine WE, the Job demand-resources theory is often applied. This study aims to see the effect of job resources (JR) and personal resources (PR) on WE and their impact on JS. This is a quantitative study that takes a cross-sectional method. The sample consisted of 244 employees of the Haji Hospital Makassar in South Sulawesi Province who were selected by random quota sampling and then analyzed using the Path Analysis test on SPSS AMOS 26. The results showed that JR (p-value 0.002<0.005, E=0.131) and PR (p-value 0.001<0.005, E=0.170) had a significant effect on WE. JR has a direct influence on JS (p-value 0.022<0.005, E=0.375). Although the indirect effect of JR on JS work engagement (WE) through is not significant (p-value 0.065<0.005), meanwhile, PR has a significant direct (p-value 0.001<0.005, E=0.248) and indirect (p-value 0.035<0.005, E=0.047) effect on JS. This study concludes that the direct influence path of PR is the best path for enhancing employee JS in hospitals.